2017
DOI: 10.3389/fpls.2017.00051
|View full text |Cite
|
Sign up to set email alerts
|

Temporally and Genetically Discrete Periods of Wheat Sensitivity to High Temperature

Abstract: Successive single day transfers of pot-grown wheat to high temperature (35/30°C day/night) replicated controlled environments, from the second node detectable to the milky-ripe growth stages, provides the strongest available evidence that the fertility of wheat can be highly vulnerable to heat stress during two discrete peak periods of susceptibility: early booting [decimal growth stage (GS) 41–45] and early anthesis (GS 61–65). A double Gaussian fitted simultaneously to grain number and weight data from two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 45 publications
4
29
0
Order By: Relevance
“…Similarly, ?50% reduction in seed weight among synthetic wheat was recorded when exposed to heat stress (35°C for 10 d) after anthesis (Yang et al, 2002). In our study, heat stress during flowering for 10 d recorded negative impact on both seed number (spike −1 ) and seed weight (spike −1 ), whereas the impact of heat stress during grain filling was more severe on seed weight, which supports earlier observations in wheat (Saini and Aspinall, 1982;Liu et al, 2016;Barber et al, 2017). The reduction in seed weight (spike −1 ) with stress during flowering was a mere reflection of the significant decline in seed number than weight per seed.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, ?50% reduction in seed weight among synthetic wheat was recorded when exposed to heat stress (35°C for 10 d) after anthesis (Yang et al, 2002). In our study, heat stress during flowering for 10 d recorded negative impact on both seed number (spike −1 ) and seed weight (spike −1 ), whereas the impact of heat stress during grain filling was more severe on seed weight, which supports earlier observations in wheat (Saini and Aspinall, 1982;Liu et al, 2016;Barber et al, 2017). The reduction in seed weight (spike −1 ) with stress during flowering was a mere reflection of the significant decline in seed number than weight per seed.…”
Section: Discussionsupporting
confidence: 89%
“…The fact that eastern landraces had larger numbers of spikes per unit area than those from the west Mediterranean countries, may be interpreted as an evolutionary adaptive mechanism to compensate for the negative effect of water scarcity on the formation of spikes. Similarly, the larger number of grains per unit area, whose potential is determined before booting (Isidro et al, 2011 ), may be a means to compensate for the degeneration of florets occurring from booting to flowering (Isidro et al, 2011 ) and the subsequent reduction in grain setting caused by heat and drought stress (Barber et al, 2017 ). The high frequency of alleles conferring a high number of spikes and grains in landraces collected in the four eastern countries (93% in both cases) may be biologically interpreted as a mechanism for achieving higher grain yield.…”
Section: Discussionmentioning
confidence: 99%
“…We found that temperature differentially affects grain formation along the spike with the middle of the spike being more sensitive to the stresses. Recent studies have shown that there are two discrete developmental stages where the spike is more sensitive to temperature: early booting when meiosis is occurring and anthesis [ 8 10 ]. Floret development along the spike is asynchronous [ 12 ] it is thus tempting to speculate that the florets in the middle were at a temperature-sensitive stage when the stress was applied.…”
Section: Discussionmentioning
confidence: 99%
“…Drought also has a significant impact on wheat yield particularly when applied during the reproductive phase [ 11 ]. The effect on yield has mainly been attributed to reduced grain number although, for some varieties and at specific growth stages, grain size could increase to compensate for this [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%